THE INFLUENCE OF GOOD CORPORATE GOVERNANCE MECHANISMS ON FINANCIAL PERFORMANCE WITH TRANSPARENCY AS A MODERATING VARIABLE IN COMPANIES LISTED ON THE INDONESIAN INDONESIA STOCK EXCHANGE IN 2020 – 2022 - Hardianti, Fitri (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
Maintaining stability is crucial for a company's overall productivity, including its financial health, workforce dynamics, and the political and social landscape in which it operates. This study aims to explore the important role of corporate governance in promoting stability and ultimately enhancing economic outcomes. The concept of good corporate governance (GCG) is highlighted as a fundamental element in guiding companies towards sustainable success. A well-defined governance framework, which includes clearly articulated mission, rules, and transparent conventions, serves as a guiding mechanism to achieve organizational objectives. To examine the relationship between corporate governance and company performance, this research utilizes the Purposive Sampling technique. Companies are selected based on strict criteria, using consecutive annual financial reports throughout the research period. The findings indicate that Variable X1 has no direct impact on Variable Y, and similarly, Variable X1 does not directly influence Variable Z. However, Variable X2 is found to indirectly influence Variable Y through its impact on Variable Z. The study emphasizes the complex relationship between corporate governance practices and various performance indicators within companies. It provides insights into the strategic considerations that can be utilized to optimize organizational productivity. Recognizing the importance of a stable operational foundation, this research advocates for the proactive adoption of sound corporate governance principles as a means to foster sustained economic improvement and propel companies towards long-lasting success.